Depiction of Indra on the eastern wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
In one corner of the rear or eastern wall of the garbhagriha (sanctum sanctorum), there is a depiction of Indra but his face and right arms have been damaged. In his upper left hand, he holds an ankusha (bullhook), while in his lower left hand, he is holding a kamandalu (water carrier or pot). The deity is accompanied by an animal. Despite the broken face, a closer examination of the animal's leg and foot confirms it to be an elephant—his mount Airavata.